PENENTUAN NILAI SPF (Sun Protection Factor) SEDIAAN LOTION EKSTRAK ETANOL KULIT ALPUKAT(Persea americana Mill.) DENGAN METODE SPEKTROFOTOMETRI UV - Sri Murni; Rafita Yuniarti, Minda Sari Lubis, Anny Sartika Daulay (Jurnal Kesehatan, 2025)
Sunscreen is a cosmetic preparation that is used to protect the skin from exposure to sunlight, thus preventing skin disorders due to exposure to sunlight. To protect the skin from the adverse effects of UV rays, protection using sunscreen is required. The purpose of this study was to determine the characteristics of the secondary metabolite simplicia contained in the ethanol extract of avocado peel, to observe the sunscreen activity of the ethanol extract of avocado peel through the SPF value and to determine the physical characteristics of the lotion preparation. The method used in this study was an experimental method. The ethanol extract of avocado peels was tested to determine the SPF value by UV spectrophotometry. Measured at a wavelength of 290-390nm with an interval of 5 nm physical quality evaluation was carried out on organoleptic tests, homogeneity, pH, viscosity, spreadability and adhesion. The results showed that avocado peel simplicia had a water content of 4.7%, a water- soluble essence of 25.5%, an ethanol-soluble extract of 22.6%, a total ash content of 3.55%, an acid-insoluble ash content of 0.5%, as a whole meeting MMI standards, containing chemical compounds in the form of flavonoids, saponins and triterpenoids. SPF test of avocado skin ethanol extract lotion made at a concentration of 0.3%; 0.36%' 0.48% with successive results of 9.974%; 9.934%; 18.8%. The overall concentration of the organoleptic lotion has a viscous form with a brownish color and rose aroma and is homogeneous, the overall pH concentration is 6, the viscosity of the lotion is 3000ppm: 2310Cp; 4000ppm: 6050Cp; 5000ppm: 8770Cp, lotion spreadability of 3000ppm concentration: 4cm; 4000ppm: 6cm; 5000ppm: 7cm, adhesion of lotion from a concentration of 3000ppm: 4.12 sec; 4000ppm: 4.39 sec; 5000ppm: 4.48 sec